1999
DOI: 10.1139/y99-085
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of liver cell membrane NHE-1, Na+-K+ATPase, and GLUT-2 protein content after cold preservation and rewarming

Abstract: Liver cell pH and volume regulation are perturbed by prolonged cold storage in University of Wisconsin solution and subsequent rewarming, but the molecular basis of this effect remains unknown. We prepared membranes from hepatocytes subjected to variable periods of cold preservation with or without subsequent rewarming and probed them by Western blotting with specific antibodies against the Na+ -H+ exchanger isoform NHE-1 and the Na+ -K+ ATPase alpha subunit. Results were compared with the content of GLUT-2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…3,4 Although it often has been shown that SECs are more sensitive to cold ischemia and warm reperfusion than parenchymal cells, 1,2 such pathophysiological conditions induce perturbations in several hepatocyte functions, observed by several laboratories, [5][6][7] including our own. [8][9][10][11][12][13] Among their numerous biological functions, liver parenchymal cells have the capacity to produce vascular endothelial growth factor (VEGF). 14 This secreted protein acts as a communication intermediate between hepatocytes and SECs to stimulate proliferation and survival of the latter cells.…”
mentioning
confidence: 99%
“…3,4 Although it often has been shown that SECs are more sensitive to cold ischemia and warm reperfusion than parenchymal cells, 1,2 such pathophysiological conditions induce perturbations in several hepatocyte functions, observed by several laboratories, [5][6][7] including our own. [8][9][10][11][12][13] Among their numerous biological functions, liver parenchymal cells have the capacity to produce vascular endothelial growth factor (VEGF). 14 This secreted protein acts as a communication intermediate between hepatocytes and SECs to stimulate proliferation and survival of the latter cells.…”
mentioning
confidence: 99%
“…153 Finally, plasma membrane expression of the glucose transporter isoform 2 was resistant to both conditions. 153 These observations highlight 2 major points. (1) The proteolytic degradation of membrane proteins may occur during simple cold storage, as also indicated in liver grafts by the presence of particular amino acids in the preservation fluid.…”
Section: Functional Disturbancesmentioning
confidence: 99%
“…151 Studies using videoplanimetric image analysis clearly showed that both regulatory volume decrease and increase were significantly blunted in isolated rat hepatocytes cultured at 37°C after cold preservation in UW solution, and this effect was preservation-time dependent. 152 This weakness in volume regulation highlights disturbances in several hepatocyte membrane transport systems, such as depressed Na ϩ /K ϩ -ATPase and Na ϩ /H ϩ exchange, 153 that may also be implicated in other homeostatic mechanisms, such as intracellular pH regulation. 154 During cold preservation, the liver undergoes metabolic acidosis as a result of the anaerobic metabolism favored by hypoxic hypothermia.…”
Section: Functional Disturbancesmentioning
confidence: 99%
See 2 more Smart Citations